A Retrospective Study of Success, Failure, and Time Needed to Perform Awake Intubation. (July 2016) - Joseph, Thomas T.; Gal, Jonathan S.; DeMaria, Samuel; Lin, Hung-Mo; Levine, Adam I.; Hyman, Jaime B.
Abstract : Background: Awake intubation is the standard of care for management of the anticipated difficult airway. The performance of awake intubation may be perceived as complex and time-consuming, potentially leading clinicians to avoid this technique of airway management. This retrospective review of awake intubations at a large academic medical center was performed to determine the average time taken to perform awake intubation, its effects on hemodynamics, and the incidence and characteristics of complications and failure. Methods: Anesthetic records from 2007 to 2014 were queried for the performance of an awake intubation. Of the 1, 085 awake intubations included for analysis, 1, 055 involved the use of a flexible bronchoscope. Each awake intubation case was propensity matched with two controls (1:2 ratio), with similar comorbidities and intubations performed after the induction of anesthesia (n = 2, 170). The time from entry into the operating room until intubation was compared between groups. The anesthetic records of all patients undergoing awake intubation were also reviewed for failure and complications. Results: The median time to intubation for patients intubated post induction was 16.0 min (interquartile range: 13 to 22) from entrance into the operating room. The median time to intubation for awake patients was 24.0 min (interquartile range: 19 to 31). The complication rate was 1.6% (17 of 1, 085 cases). The most frequent complications observed were mucous plug, endotracheal tube cuff leak, and inadvertent extubation. The failure rate for attempted awake intubation was 1% (n = 10). Conclusions: Awake intubations have a high rate of success and low rate of serious complications and failure. Awake intubations can be performed safely and rapidly. Abstract : This large retrospective analyses of 1, 085 awake intubations performed in an academic hospital revealed that awake fiberoptic intubation added approximately 8 min of time in the operating room compared to asleep intubation techniques. Awake intubation was successfully performed with low failure rate (1%) and low complication rate (1.6%) under hemodynamically stable conditions.